Risk Factors for Postpartum Hemorrhage and its Severe Forms with Blood Loss Evaluated Objectively - A Prospective Cohort Study - Borovac-Pinheiro,Anderson (2021)
Abstract Objective To identify risk factors related to postpartum hemorrhage (PPH) and severe PPH with blood loss quantified objectively. Methods This is a complementary analysis of a prospective cohort study that included pregnant women delivering vaginally. The total blood loss was obtained through the sum of the volume collected from the drape with the weight of gauzes, compresses and pads used by women within 2 hours. Exploratory data analysis was performed to assess mean, standard deviation (SD), frequency, percentage and percentiles. The risk factors for postpartum bleeding were evaluated using linear and logistic regression. Results We included 270 women. Themean blood loss at 120 minutes was 427.49 mL (±335.57 mL). Thirty-one percent (84 women) bled > 500mL and 8.2% (22 women) bled > 1,000 mL within 2 hours. Episiotomy, longer second stage of labor and forceps delivery were related to blood loss > 500mL within 2 hours, in the univariate analysis. In the multivariate analysis, only forceps remained associated with bleeding > 500 mL within 2 hours (odds ratio [OR] = 9.5 [2.85-31.53]). Previous anemia and episiotomy were also related to blood loss > 1,000mL. Conclusion Prolonged second stage of labor, forceps and episiotomy are related to increased incidence of PPH, and should be used as an alert for the delivery assistants for early recognition and prompt treatment for PPH.